Techno-economic optimisation of level and raise spacing range in planning a Bushveld Complex platinum reef conventional breast mining layout - Musingwini, Cuthbert (My University, 2010)
The Bushveld Complex in South Africa is a geological formation that hosts approximately 87% of all the known world platinum group metal (PGM) resources and reserves. It produces about 77% of the world’s primary platinum production. However, the sheer size of the resources and reserves obscures the fact that the PGM mineral resources are a wasting asset, and should therefore be extracted optimally in order to ensure sustainable production. In addition, a 2006 survey of research and development (R&D) needs of the South African platinum mining companies by the CSIR-Miningtek, noted that out of 19 possible R&D areas, layout optimisation is one of the top four priority R&D focus areas. Section 51 of the Mineral and Petroleum Resources Development Act (MPRDA) of 2002, of South Africa, also emphasises that owners of mining rights should optimally extract mineral resources. About 70% of the platinum production from the Bushveld Complex is extracted using conventional mining methods, while the remainder comes from hybrid and mechanised mining methods. It was therefore prudent to focus on optimising conventional mining layouts. Optimisation in mining broadly requires extracting the maximum amount of ore by excavating and moving the minimum amount of waste in the shortest possible time and in the safest and most environmentally acceptable manner. In open-pit mine planning, this broadly requires minimising the waste stripping ratio, while in underground mine planning it principally requires minimising the metres of waste development. A literature review revealed that minimising waste development in conventional breast mining is predominantly achieved by increasing level and raise spacing. However, when level and raise spacing are increased, other factors such as productivity are negatively affected, thus requiring a delicate trade-off of contradicting factors. This characterises the problem as a multi-criteria optimisation process that should be solved using multi-criteria decision analysis (MCDA) techniques. The Analytic Hierarchy Process (AHP) was the most appropriate MCDA methodology for solving the problem of optimising level and raise spacing. By using real geological data on the orebody code-named OB1 that was typical of Bushveld Complex platinum reef deposits, the optimal range of vertical level spacing derived was 30m-50m, while the optimal range of raise spacing was 180m-220m. The layout designs and schedules were done in Mine2-4D® and EPS® software suite, which is one of the mine design and planning software currently used by the South African platinum mining industry for long-term mine planning. The research methodology used in this thesis and the results obtained were received positively by the South African platinum mining industry because for the first time in several decades, a holistic methodology and practically acceptable solution had been obtained for the controversial debate of optimising level and raise spacing for conventional mining layouts.